Morphological characters of newborns in relation to certain biological properties of mothers - Mucha, Ewa (Anthropological Review, 1980)
The purpose of this study was to investigate relation between morphology of newborns and following factors: mother's age, parity, mode of birth and a number of unsuccessful pregnancies prior to a given birth. The material used for investigations comprised information on 788 male and 789 female newborns born during 1969 contained in archives of Obstetrics and Gynecology Clinic, Poznań Medical School. It has been found that mother's age has slight influence on newborn morphology. Parity influence can be relevant only with respect to comparison between first born and other newborns. First-born individuals are smaller than others. Mode of birth and unsuccessful pregnancies occuring prior to a given birth have no relation to newborn morphology.